Evaluation of Intra-examiner Variability in Video Head Impulse Test Results - GEÇİCİ, CENNET REYYAN; DERİNSU, EMİNE UFUK; CESUR, SIDIKA (AMER ACAD AUDIOLOGY, 2020)
Objective The video head impulse test (vHIT) is a diagnostic tool to assess the function of the semicircular canals and branches of the vestibular nerve. The aim of this study was to analyze the inter-examiner variability of vHIT results in healthy subjects. Materials and Methods A total of 21 healthy participants were included in the study. vHIT responses were collected by four clinicians. Variability of the vHIT results between examiners was analyzed statistically. Results The vestibulo-ocular reflex (VOR) velocity regression values were from 0.99 to 1.09 degrees per second for the lateral canals. For the vertical canals, VOR velocity regression values were from 0.87 to 1.21 degrees per second. According to repeated measures analysis of variance, the normality assumptions for the velocity regression of the left lateral canal (p = 0.002) and the right anterior canal (p < 0.01) were met and the differences were statistically significant. The normality assumptions were not met for 40, 60, and 80 ms median gain of the right lateral canal (p = 0.016, p = 0.038, and p = 0.001, respectively); 40 and 60 ms median gain of the left lateral canal (p < 0.001 and p = 0.008, respectively); and the velocity regression of the left posterior canal (p < 0.00). These differences were found to be statistically significant by using the Friedman test. Conclusion The inter-examiner differences of the VOR gain values for the vHIT were statistically significant. Serial vHIT testing should be performed by the same examiner to reduce the effects of inter-examiner variability.
Keywords: video head impulse test; inter-examiner variability; vestibulo-ocular reflex gain; TEST DIAGNOSTIC-ACCURACY; TEST-RETEST RELIABILITY; VESTIBULOOCULAR REFLEX